Accurate computed spin-state energetics for Co(iii) complexes: implications for modelling homogeneous catalysis. Issue 19 (4th May 2020) - Neale, Samuel E.; Pantazis, Dimitrios A.; Macgregor, Stuart A.
Abstract : DLPNO-CCSD(T) calculations provide accurate spin state energetics for a range of Co(iii ) complexes and so represent a promising approach to modelling homogeneous catalysis based on Co(iii ) species. Abstract : Co(iii ) complexes are increasingly prevalent in homogeneous catalysis. Catalytic cycles involve multiple intermediates, many of which will feature unsaturated metal centres. This raises the possibility of multi-state character along reaction pathways and so requires an accurate approach to calculating spin-state energetics. Here we report an assessment of the performance of DLPNO-CCSD(T) (domain-based local pair natural orbital approximation to coupled cluster theory) against experimental 1 Co to 3 Co spin splitting energies for a series of pseudo-octahedral Co(iii ) complexes. The alternative NEVPT2 (strongly-contracted n-electron valence perturbation theory) and a range of density functionals are also assessed. DLPNO-CCSD(T) is identified as a highly promising method, with mean absolute deviations (MADs) as small as 1.3 kcal mol −1 when Kohn–Sham reference orbitals are used. DLPNO-CCSD(T) out-performs NEVPT2 for which a MAD of 3.5 kcal mol −1 can be achieved when a (10, 12) active space is employed. Of the nine DFT methods investigated TPSS is the leading functional, with a MAD of 1.9 kcal mol −1 . Our results show how DLPNO-CCSD(T) can provide accurate spin state energetics for Co(iii ) species in particular and first row transition metal systems in general. DLPNO-CCSD(T) is therefore a promising method for applications in the burgeoning field of homogeneous catalysis based on Co(iii ) species.